Effects of memory cue and interest in remembering and forgetting of gist and details - Hu, Zhongyu; Yang, Jiongjiong (Frontiers in Psychology, 2023)
The gist and details of an event are both important for us to establish and maintain episodic memory. On the other hand, episodic memory is influenced by both external and internal factors, such as memory cue and intrinsic motivation. To what extent these factors and their interaction modulate memory and forgetting of gist and detailed information remains unclear. In this study, 29 participants watched film clips accompanied by either gist or detailed cues and rated their interest in these clips. Their memories of gist and detailed information were tested after 10 min, 1 day, and 1 week. The results showed that memory cue modulated the forgetting of gist and detailed memories. Specifically, when gist cues were used, gist memory was forgotten more slowly than detailed memory. When detailed cues were used, detailed memory was forgotten more slowly than gist memory. Differently, the subjective interest in the clips enhanced memory accuracy irrespective of memory type but did not influence the forgetting of gist and detailed memories. Moreover, there was a significant interaction between memory cue and interest, showing that gist cues enhanced memory than detailed cues only for low-interest clips. These results suggest that external and internal factors have differential effects on memory and forgetting, and the effectiveness of external factors depends on the state of intrinsic motivation. The significant interplay of different factors in influencing the remembering or forgetting of gist and detailed memories provides potential ways to enhance memory and retention of gist and detailed information.